2012
DOI: 10.1016/j.jcis.2011.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of agarose-based chromatographic adsorbents – Effect of ionic strength and cooling conditions on particle structure and mechanical strength

Abstract: The effect of ionic strength of agarose solution and quenching temperature of the emulsion on the structure and mechanical strength of agarose-based chromatographic adsorbents was investigated. Solutions of agarose containing different amounts of NaCl were emulsified at elevated temperature in mineral oil using a high-shear mixer. The hot emulsion was quenched at different temperatures leading to the gelation of agarose and formation of soft particles. Analysis of Atomic Force Microscopy (AFM) images of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
5
0
2
Order By: Relevance
“…After the fibers mature development, the lower cooling rate will not affect the pore structure. The trends in mean pore size and pore size uniformity of the agarose media as a function of cooling rate are in accordance with previous literatures [13,14]. However, our results are more accurate and finer changes could be distinguished than in other studies.…”
Section: Effect Of Cooling Rate On the Agarose Media Pore Size Uniforsupporting
confidence: 93%
See 2 more Smart Citations
“…After the fibers mature development, the lower cooling rate will not affect the pore structure. The trends in mean pore size and pore size uniformity of the agarose media as a function of cooling rate are in accordance with previous literatures [13,14]. However, our results are more accurate and finer changes could be distinguished than in other studies.…”
Section: Effect Of Cooling Rate On the Agarose Media Pore Size Uniforsupporting
confidence: 93%
“…Loannidis et al. quenched the hot agarose emulsion at different temperature leading to the gelation of the agarose and the formation of soft particles. Characterization by atomic force microscopy (AFM) of the particle surfaces showed that the particle pore size increased when subjected to high quenching temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial agarose powder is manufactured using a range of different methods, including spray drying, suspension gelation and membrane emulsification and is generally polydisperse [20,21]. To create agarose microparticles, we used a fluidic system that is similar to an approach described for interfacial polymeriza-tions in liquid prepolymer droplets [19].…”
Section: Resultsmentioning
confidence: 99%
“…Agarose hydrogels form upon cooling, and the final gel structure and pore size distribution are affected by the cooling rate. 38,39 In the current study, the gel was formed with rapid cooling over 30 min from 72 to 30 °C, followed by a very slow cooling phase until the hydrogel reached 22 °C (the cooling curve was previously published 9 ). Separate agarose gels prepared from agarose solutions of various concentrations (0.38–2.0% w/v) are referred to as agarose gels of the respective concentration.…”
Section: Methodsmentioning
confidence: 85%